Gender attitudes in agriculture and positivity bias: A survey experiment in four countries in Sub-Saharan Africa - Ragasa, Catherine; Lambrecht, Isabel B.; Ma, Ning; Cole, Steven; Ebrahim, Mohammed; Desta, Gizaw; Mersha, Abiro Tigabie; Mudereri, Bester; Kihiu, Evelyne; Kreye, Christine; Peter, Hellen (International Food Policy Research Institute, 2025)
Extensive prior research has demonstrated that reducing gender discrimination enhances women’s empowerment, promotes more inclusive livelihoods, increases agricultural productivity, and improves other development outcomes. This study aims to contribute to documenting and informing the measurement of gender attitudes that relate directly to reaching, benefiting, and empowering women through agricultural innovations. By analyzing data from 8,051 survey respondents across study sites in Democratic Republic of the Congo, Ethiopia, Nigeria, and Rwanda, our findings emphasize both commonalities and differences in gender attitudes across different contexts. Furthermore, by including a survey-based experiment during data collection, we assess whether gender-attitude statements vary depending on whether they are presented in a positive frame (focusing on equality) or in a negative frame (focusing on inequality). On average, rural women and men respondents across all countries supported more than half of the gender-equality statements. Some gender-inequality attitudes persisted across the four countries but varied in magnitude and by location, age group, and specific statement or theme. Framing matters: respondents exposed to a positive framing supported 16 percent more gender-equality statements than those exposed to a negative framing. The study highlights two main implications. First, the findings indicate the importance of considering both restrictive attitudes and those that reflect gender-equality opportunities as being in the vanguard. Accordingly, gender-focused interventions should adopt strategies that challenge normative views of women as supporting rather than leading actors in agriculture and economic activities. Second, gender-attitude measures do not perfectly align with country-level gender-equality indicators or with empowerment at the intrahousehold level. They therefore capture a distinct dimension and merit their own indicators.